Comparing the efficacy of the monocular trial treatment paradigm with multiple measurements of intraocular pressure before and after treatment initiation in primary open-angle glaucoma - Krishna R (Dove Medical Press, 2012)
Rohit Krishna, Peter W DeBry, Corey W Waldman, Peter KoulenVision Research Center, Department of Ophthalmology, University of Missouri-Kansas City School of Medicine, MO, USAAbstract: The monocular trial has been proposed as a test to help control for diurnal fluctuations in eye pressure when assessing medication effectiveness. We undertook a prospective study to determine the sensitivity and specificity of the monocular trial as a test for determining the effectiveness of a glaucoma medication. The efficacy of the monocular trial was compared to the diagnostic paradigm of repeated pre- and post-treatment measurements in determining whether an intraocular pressure (IOP)-lowering drug is effective. Forty-two patients with newly diagnosed open-angle glaucoma completed five visits: visit 1 for determining eligibility, obtaining consent, and measuring IOP, visit 2 for a second pressure measurement, and visit 3 for a third pressure reading. The new medication was then started in one eye. IOP measurements were made at weeks 4 and 6. The gold standard IOP change was defined as the difference in mean between the pre- and post-medication visits. A medication was deemed effective if this difference was at least 15%. The monocular trial pressure change was defined as the IOP change in the treated eye between the visit immediately before and immediately after the medication addition, corrected by subtracting the pressure change in the untreated eye. All 42 patients completed the full protocol with good compliance. Twenty-five of 42 (60%) medication additions were considered effective by the gold standard method, and 25/42 (60%) by the monocular trial method. However, the two methods agreed in only 26 patients (17 Yes/Yes, nine No/No). The calculated sensitivity was low (0.68), with a specificity of 0.53. The monocular trial can give useful clues as to whether a medication is effective, but should not be the only information used in making this determination. To obtain the most valid results, multiple pressure checks should be done before and after starting a new medication.Keywords: applanation tonometry, visual field, eye, vision, glaucoma, pharmacology